TRPML1 and RAS-driven cancers – exploring a link with great therapeutic potential. Issue 1 (1st January 2019) - Jung, Jewon; Venkatachalam, Kartik
ABSTRACT: Activating mutations in the RAS family of proto-oncogenes represent some of the leading causes of cancer. Unmitigated proliferation of cells harboring oncogenic RAS mutations is accompanied by a massive increase in cellular bioenergetic demands, which offers unique opportunities for therapeutic intervention. To withstand the steep requirements for metabolic intermediates, RAS-driven cancer cells enhance endolysosome and autophagosome biogenesis. By degrading cellular macromolecules into metabolites that can be used by biosynthetic pathways, endolysosomes permit continued proliferation and survival in otherwise detrimental conditions. We recently showed that human cancers with activating mutations in HRAS elevate the expression of MCOLN1, which encodes an endolysosomal cation channel called TRPML1. Increased TRPML1 activity in HRAS-driven cancer cells is needed for the restoration of plasma membrane cholesterol that gets collaterally internalized during endocytosis. Inhibition of TRPML1 or knockdown of MCOLN1 leads to mislocalization of cholesterol from the plasma membrane to endolysosomes, loss of oncogenic HRAS from the cell surface, and attenuation of downstream signaling. Here, we discuss the implications of our findings and suggest strategies to leverage pathways that impinge upon TRPML1 as novel anti-cancer treatments.